Problems in current CAD systems. (4th November 2010) - Matsuki, Norio
In this paper, problems of current computer aided design (CAD) systems are discussed. One problem is the existence of tolerance. Because of tolerance, geometric operations become unstable and CAD data-exchange becomes a troublesome task. The second problem is CAD data durability. There is almost no compatibility between CAD data of different versions of the same system. Thus, users of CAD systems are confronted with great difficulties when they try to keep CAD data for a long time. As a solution to these problems, a CAD kernel based on history-based parametrics is proposed.